2017
DOI: 10.1038/s41598-017-14692-3
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology exploration reveals endothelial inflammation as a common mechanism for stroke and coronary artery disease treatment of Danhong injection

Abstract: Although Danhong injection (DHI) is the most widely prescribed Chinese medicine for both stroke and coronary artery disease (CAD), its underlying common molecular mechanisms remain unclear. An integrated network pharmacology and experimental verification approach was used to decipher common pharmacological mechanisms of DHI on stroke and CAD treatment. A compound-target-disease & function-pathway network was constructed and analyzed, indicating that 37 ingredients derived from DH (Salvia miltiorrhiza Bge., Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 122 publications
2
43
0
Order By: Relevance
“…In the vascular endothelium, DHI attenuates lipopolysaccharides (LPS) and oxidized LDL (oxLDL) induced secretion of tumor necrosis factor-α (TNF-α), interleukin 1 β (IL-1β), and interleukin 10 (IL-10), by inhibiting the activation of p38, nuclear factor-kappa B (NF-κB), and c-jun. This may be a potential mechanism for DHI to protect against stroke and coronary heart disease [10]. DHI attenuates hypoxic damage in brain microvascular endothelial cells.…”
Section: Experimental Studies and Molecular Mechanismsmentioning
confidence: 98%
See 2 more Smart Citations
“…In the vascular endothelium, DHI attenuates lipopolysaccharides (LPS) and oxidized LDL (oxLDL) induced secretion of tumor necrosis factor-α (TNF-α), interleukin 1 β (IL-1β), and interleukin 10 (IL-10), by inhibiting the activation of p38, nuclear factor-kappa B (NF-κB), and c-jun. This may be a potential mechanism for DHI to protect against stroke and coronary heart disease [10]. DHI attenuates hypoxic damage in brain microvascular endothelial cells.…”
Section: Experimental Studies and Molecular Mechanismsmentioning
confidence: 98%
“…DHI is a composite formula of two eminent Chinese herbal medicine-Salviae Miltiorrhizae (Dan Shen) and Flos Carthami (Hong Hua). Compared with single-target western medicine, DHI is a multi-component and multi-target medicinal preparation, which indicates that DHI may have a wider range of clinical applications [10,86,106].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [83] have reported that treatment with DHI for 7 days alleviates the formation of abdominal adhesion by inhibiting inflammation, collagen deposition, and oxidative stress in a rat model. DHI has been extensively used in clinical practices for a long time, which supported to serve as a promising drug to prevent PAA [84].…”
Section: Danhong Injection Danhong Injection (Dhi) Is Amentioning
confidence: 99%
“…DAVID provides high-throughput functional annotation bioinformatics to perform functional annotation and enrichment analysis. e cutoff of recognized GO terms is set to FDR < 0.01 and KEGG pathways is set to P value <0.05 [26,27].…”
Section: Gene Ontology and Pathway Enrichment Analysismentioning
confidence: 99%